Molecular Characterization Of B-Lβ Ii Family Alleles In Caribro-Vishal Chicken By Pcr-Ssp - Thakur, Mohan Singh; Parmar, Shivnandan Singh; Jha, Amit Kumar; Tomar, Satyendra Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The present study was planned to investigate the polymorphism of MHC B-Lβ II family (class II) alleles and genotyping using one of the variants of polymerase chain reaction (PCR), the PCR SSP (Polymerase Chain Reaction with sequence specific primers) in Caribro-Vishal (Caribro-91) chickens. Genomic DNA was isolated from blood of 30 birds maintained at experimental poultry unit at College of Veterinary Science and Animal Husbandry, Jabalpur. A 235 bp, exon-2 region of chicken MHC B-Lβ ΙΙ family was amplified using a set of degenerating primers. The amplicons of the first round of amplification were subjected to PCR-SSP at the specified annealing temperatures and replication cycles. The primers designed for B2, B13, B15, B19 and B21 haplotypes amplified the target sequences producing a 222 bp, 141 bp, 222 bp, 213 bp and 213 bp fragments, respectively. The findings of the research revealed 10 genotypes. It was observed that the alleles B19 and B15 exhibited predominance in this genetic group. Moreover, genotypic distribution also revealed higher occurrence of B15B19, B19B19 and B15B15 heterozygotes in the studied population. The highly significant Chi-square values (P<0.01) showed that the selected population of birds was not in Hardy Weinberg equilibrium.